Analisis Sosiologi Politik dalam Pemenangan Pasangan Calon Mohammad Idris dan Imam Budi Hartono pada Pilkada 2020 di Kota Depok - Ramadhan, Arief Fadillah; Ridwan , Ridwan (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
The victory of the candidate pair Mohammad Idris and Imam Budi Hartono in the 2020 Depok City Regional Election created substantial political dynamics at the local level. The background of the candidate pair, holding incumbent status, provided advantages in terms of track record, knowledge, public figure status, and popularity, which could shape social support as a political campaign tool. The utilization of social support as a political instrument was reinforced through a religious approach by leveraging figures and community groups to form social networks. Through the formation of social networks within the community, the candidate pair could formulate policy programs aligned with the community's needs. This research aims to analyze the sociopolitical aspects related to the phenomenon of community decision-making contributing to the victory of the candidate pair. The research method used was descriptive qualitative, utilizing two types of data sources: primary data obtained through structured interviews and secondary data including books, statistical data of Depok City, and relevant previous research. The research findings indicate that sociopolitical factors such as political identity, economy, religion, and social dynamics play significant roles in shaping the victory of the candidate pair Mohammad Idris and Imam Budi Hartono in the 2020 Depok City Regional Election. The findings from this research provide an in-depth understanding of the importance of comprehending the interplay of sociopolitical factors in understanding political phenomena at the local level.